Vena Cava Superior Syndrome Related to Right Heart Invasion of an Unresectable Hepatocellular Carcinoma - Geert Maleux; Werner Budts; Vincent Vandecaveye (Canadian Journal of Gastroenterology and Hepatology)
A rare case of hepatocellular tumor extension in the right heart was reported. The patient presented with clinical signs of a vena cava superior syndrome. Computed tomography and transthoracic echocardiography demonstrated a large tumoral mass lesion extending from the left liver lobe into the inferior vena cava right atrium and right ventricle. The patient was treated with best supportive care.